Analysis of intestinal flora in elderly Uygur patients with sarcopenia - Zimei Shan; Na Cheng; Jia Zhu; Fei Chen; Jiani Ji; Meilibana (Immunity, Inflammation and Disease, 2024)
Abstract Objective This study was designed to analyze the structural characteristics of the intestinal flora of elderly Uygur patients with sarcopenia, thereby providing new ideas for clinical treatment. Methods Firstly, fecal samples were collected from 40 elderly Uygur patients with sarcopenia (Sarcopenia group) and 40 healthy people (Control group). Next, significant differences in the intestinal flora between the two groups were analyzed based on 16S rDNA high‐throughput sequencing. The linear discriminant analysis effect size (LEfSe) was used to estimate the magnitude of the effect of each component (species) abundance on the differential effect. Additionally, an analysis was also performed on the relationship between the intestinal flora and the cytokines in the peripheral blood of patients with sarcopenia. Results The results of β diversity showed that there were differences in the structure of the intestinal flora between the two groups. Besides, the phylum level of intestinal flora between the two groups was not significantly different. However, the difference was significant in the intestinal flora at the order, family, and genus levels between the two groups. Among them, Lachnoclostridium, Photobacterium, Anaerobic Bacillus, Hydrogenophilus, and Eubacterium were enriched in the Sarcopenia group; Prevotella 9, Firmicutes FCS020 group, Streptobacillus, Aggregatibacter, Corynebacterium, Clostridium Difficile, and Haloanaerobium were enriched in the Control group. The LEfSe outcomes further showed that Lachnoclostridium was highly enriched in the Sarcopenia group; Prevotella 9 and Firmicutes FCS020 group were significantly enriched in the Control group. Furthermore, the relative abundance of Lachnoclostridium and Streptobacillus were significantly different in patients with high and low IL‐6 levels. Conclusion In conclusion, Lachnoclostridium is significantly enriched in the intestines of elderly Uygur patients with sarcopenia; the increase in Lachnoclostridium abundance and the decrease in Streptobacillus abundance are associated with high levels of IL‐6. Therefore, abnormal intestinal flora is related to inflammatory reflexes in patients with sarcopenia.